Emergency surgery for perforated gastric malignancy: An institution’s experience and review of the literature - Tan, Ker-Kan (Pioneer Bioscience Publishing Company, 2011)
OBJECTIVES: The aim was to evaluate the outcome of patients who underwent surgery for perforated gastric malignancies. METHODS: A review of all patients who underwent surgery for perforated gastric malignancy was performed. RESULTS: Twelve patients (nine gastric adenocarcinoma and three B-cell lymphoma) formed the study group. Ten (83.3%) had subtotal gastrectomy performed, while two (16.7%) underwent total gastrectomy. All eight patients with adenocarcinoma who survived the initial operation fared poorly. The two patients with lymphoma who survived the surgery underwent subsequent chemotherapy has no disease recurrence currently. CONCLUSION: Surgery in perforated gastric malignancy is fraught with numerous challenges.